AN ANALYTICAL STUDY OF ALEKSANDR FAYNBERG’S POEM “LOOK FROM THE BOTTOMLESS SEA” - Zoirova Diyora (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Introduction. Modern Uzbek–Russian poetry has long been enriched by poets who explore the human spirit, the subtle shades of emotion, and the symbolic relationship between nature and the inner world. Among such prominent figures stands Aleksandr Faynberg (1946–2021), a poet widely known for his gentle lyricism, spiritual depth, and universal humanistic worldview. His works often merge personal experience with abstract reflections on life, time, and memory, creating a poetic landscape where nature acts as both companion and witness to human emotion. The poem “Look from the Bottomless Sea” (Tubi yo‘q dengizdan boq) presents one of Faynberg’s most delicate lyrical meditations. Through natural images such as the sea, stars, leaves, and wind, the poet constructs a symbolic dialogue between the lyrical hero and the world. The poem is not merely descriptive; it reveals a deep emotional structure in which poetry becomes a space for spiritual purification and connection with future generations.